Dietary licorice enhances in vivo cadmium detoxification and modulates gut microbial metabolism in mice. Issue 1 (10th March 2022) - Zheng, Xin; Wang, Likun; You, Linhao; Liu, Yong‐Xin; Cohen, Michael; Tian, Siyu; Li, Wenjun; Li, Xiaofang
Abstract: Mass cadmium (Cd) poisoning is a serious health problem in many parts of the world. We propose that dietary intervention can be a practical solution to this problem. This study aimed to identify effective dietary products from traditional Chinese herbs that can detoxify Cd. Five candidate herbal foods with detoxifying potential were selected and subjected to mouse toxicological tests. The chemical composition and dose–response effects of licorice on mouse hepatocytes were determined. Licorice was selected for further tests to examine its effects on growth, tissue Cd accumulation, and gut and liver fitness of mice. The expression of hepatic metallothionein (Mt) genes was quantified in vitro in hepatocytes and in vivo in liver tissues of mice. The results showed that licorice dietary intervention was effective in reducing blood Cd by >50% within 1 month. Cd was also substantially reduced in the heart and lung tissues, but increased 2.1‐fold in the liver. The liver of Cd poisoned mice improved with licorice intervention. Licorice treatment significantly induced Cd accumulation and expression of the Mt1 gene in hepatic cells both in vitro and in vivo. Licorice intake substantially altered gut microbial structure and enriched Parabacteroides distasonis . Omics results showed that licorice improved gut metabolism, particularly the metabolic pathways for glycyrrhizin, bile acids, and amino acids. Dietary licorice effectively reduced mouse blood Cd and had a profound impact on liver and gut fitness. We conclude that herbal licorice can be used as a dietary intervention for mass Cd poisoning. Abstract : We propose that dietary intervention can be a solution to mass Cd poisoning. Dietary licorice effectively reduced mouse blood Cd by >50% within a month. Licorice intake induced Cd accumulation and Mt1 expression in mice liver. Licorice intake modulated mice gut microbiota and metabolism. Overall dietary licorice substantially improved mice fitness under Cd stress. Highlights: We propose that dietary intervention can be a solution to mass Cd poisoning. Dietary licorice effectively reduced mouse blood Cd by >50% within a month. Licorice intake induced Cd accumulation and Mt1 expression in mice liver. Licorice intake modulated mice gut microbiota and metabolism. Overall dietary licorice substantially improved mice fitness under Cd stress.